Ammonia nitrogen adsorption material capable of being used for soil improvement as well as preparation method and application of ammonia nitrogen adsorption material
By co-pyrolyzing straw debris and zeolite powder and NaOH modification, an efficient NH4+-N adsorbent material was prepared, which solved the problems of high consumption of adsorbent materials and difficulty in treating waste materials in low-concentration NH4+-N wastewater treatment, and achieved the dual effects of deep nitrogen denitrition and soil improvement.
Patent Information
- Application Number
- CN202411944241.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-12-27
AI Technical Summary
The prior art has problems such as high consumption of adsorbent materials and difficulty in treating waste materials in low-concentration NH4+-N wastewater treatment, and the adsorbents prepared by a single material have disadvantages in terms of effectiveness and cost.
By mixing straw debris with zeolite powder in a specific proportion, co-pyrolysis and NaOH modification, a loaded zeolite biochar material with high NH4+-N adsorption capacity was prepared for deep denitrification treatment of low-concentration NH4+-N wastewater, and the adsorbed material was regenerated and utilized as a soil improver.
It has achieved efficient nitrogen removal treatment of low-concentration NH4+-N wastewater, and used the materials after adsorption of nitrogen for soil improvement, which has improved the physical and chemical properties of the soil, promoted the germination and growth of plants, and achieved the synergistic effect of waste reuse and sewage pollution control.
Smart Images

Figure CN119549114A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of environmental protection, and in particular relates to an ammonia nitrogen adsorption material that can be used for soil improvement, and a preparation method and application thereof. Background Art
[0002] Adding biochar to soil can improve the physical, chemical and biological properties of soil, which is beneficial to soil improvement and restoration. Biochar can increase soil organic matter content, cation exchange capacity, permeability and microbial activity, and increase the formation of soil aggregate structure. In particular, biochar has adsorption properties for soil nutrients nitrogen, phosphorus and potassium, which can alleviate the loss of soil nutrients, reduce agricultural nitrogen and phosphorus non-point source pollution, improve soil fertility and promote crop growth. For example, rice straw charcoal has good adsorption performance for nitrogen, phosphorus and potassium, and its adsorption capacity can reach (2.44±0.15) mg / g, (2.91±0.12) mg / g and (4.97±0.22) mg / g respectively, with outstanding carbon fixation potential and farmland effect.
[0003] On the other hand, biochar is used for low concentration NH4 + -N wastewater adsorption deep denitrification treatment technology has also been widely studied. Biochar and activated carbon adsorption are similar, and can achieve NH4 through surface ions and chemical functional groups through ion exchange, chemical precipitation and coordination. + The adsorption of NH4 + -N removal effect, but the adsorption capacity of biochar prepared from different materials for wastewater of different concentrations varies. For example, studies have shown that Enteromorpha biochar is used for water treatment containing 10.00 mg / L ammonia nitrogen, with a maximum adsorption capacity of 16.76 mg / g; rape straw biochar is used for water treatment containing 30.00 mg / L ammonia nitrogen, with a maximum adsorption capacity of 12.51 mg / g; Chlorella-peanut shell co-pyrolysis biochar is used for water treatment containing 5.00 mg / L ammonia nitrogen, with a maximum adsorption capacity of 4.84 mg / g. Although the adsorption method is effective at low concentrations of NH4 + -N shows good results in wastewater treatment, but the subsequent resource utilization and cost issues still need to be considered, especially for large-scale sewage treatment, which requires a large amount of adsorption materials and faces the problem of treatment and disposal of waste materials. Therefore, in practical applications, it is still necessary to comprehensively consider the cost and the feasibility of its application.
[0004] Zeolite is an aluminum silicate mineral (chemical formula: M x / n [(AlO2) x (SiO2) y ]·mH2O], M represents metal cations such as sodium, calcium, potassium, etc. It is a mineral material with orderly and uniform through-holes and a large specific surface area, and has the ability to exchange cations and adsorb NH4+ -N potential, studies have shown that zeolite adsorption can remove NH4 from landfill leachate + The maximum adsorption capacity of -N can reach 15.5mgNH4 + -N / g zeolite.
[0005] At present, there is technology to use modified biochar or zeolite to prepare nitrogen and phosphorus adsorbents and apply them to the soil as soil conditioners ([1] Duan Qinglong. Adsorption effect and simulation analysis of modified biochar on ammonia nitrogen and total phosphorus in simulated sewage [D]. Northeast Agricultural University, 2022. DOI: 10.27010 / d.cnki.gdbnu.2022.000788; [2] Mark Rave. Application of zeolite in environmental protection [D]. Guangxi Normal University, 2019), but it has disadvantages in effect and cost when used as a single material to prepare adsorbents. At present, there is also technology to mix biochar and zeolite as a composite matrix for artificial wetlands to adsorb NH4 + -N ([3]Xu Jianling, Zou Li, Wang Xinyu, et al. An artificial wetland with plants and composite matrix under low-temperature intermittent aeration [P]. Hainan Province: CN202410841669.7, 2024-10-25), but there has been no literature or patent disclosure reporting the use of zeolite and biochar or activated carbon in combination for soil improvement. Summary of the invention
[0006] In order to overcome the shortcomings of the prior art, the present invention aims to provide an ammonia nitrogen adsorption material that can be used for soil improvement, a preparation method and application thereof, and to prepare an ammonia nitrogen adsorption material with high NH4 by co-pyrolysis of zeolite and waste agricultural straw. + -N adsorption capacity of the composite material, enabling efficient denitrification of low-concentration domestic sewage and adsorption of NH4 + -N composite materials can be further recycled as soil conditioners, and the addition of zeolite is expected to increase the biochar material's NH4 + -N adsorption performance, and its naturally loose and porous mineral properties also make it feasible for soil improvement.
[0007] In order to achieve the above object, the present invention adopts the following technical solutions:
[0008] An ammonia nitrogen adsorption material that can be used for soil improvement, the raw materials of which include straw chips and zeolite powder in a mass ratio of 7:3-9:1.
[0009] The straw debris is corn stalks, which are air-dried and stored at room temperature after being collected. Before preparing biochar, they are dried overnight, crushed and sieved through an 80-120 mesh sieve to obtain straw debris.
[0010] The zeolite is natural clinoptilolite, which is ground and passed through a 170-230 mesh sieve to obtain zeolite powder.
[0011] A method for preparing an ammonia nitrogen adsorption material that can be used for soil improvement comprises the following steps:
[0012] S1. Evenly mixing straw scraps and zeolite powder to obtain a mixed raw material, wherein the mass ratio of straw scraps to zeolite powder is 7:3-9:1;
[0013] S2, the mixed raw materials obtained in step S1 are placed in a high temperature tube furnace for co-pyrolysis at 10 ° C. min -1 The temperature of the furnace is raised to 500-750°C with a temperature gradient of 100°C and kept at this temperature for 1-2 hours, during which nitrogen is introduced as a protective gas to isolate oxygen; during the pyrolysis process, zeolite and corn stalks undergo a co-pyrolysis reaction to obtain a composite co-pyrolysis product;
[0014] S3, adding 0.1-0.3% of the composite co-pyrolysis product obtained in step S2 to a 1 mol / L NaOH solution, stirring evenly at 20-25°C and 100-140 r·min -1 After being shaken and immersed for 22 to 26 hours under the conditions of , it is taken out, repeatedly washed with deionized water until it becomes neutral, and placed in a drying oven for drying to obtain an alkali-modified product, i.e., an ammonia nitrogen adsorption material.
[0015] The composite co-pyrolysis product is heated at 20-25°C and 100-140 r / min. -1 Under the condition of 22~26h, 20mg·L -1 NH4 + -N solution NH4 + The maximum adsorption capacity of -N is 16.84~17.22mg / g.
[0016] The alkali-modified product is heated at 20-25°C and 100-140 r·min. -1 Under the condition of 22~26h, 20mg·L -1 NH4 + -N solution NH4 + The maximum adsorption capacity of -N is 17.89-19.08 mg / g.
[0017] The application of the ammonia nitrogen adsorption material that can be used for soil improvement is to adsorb NH4 + -N-containing materials are added to the soil to improve soil properties and promote plant germination and growth.
[0018] The application method comprises the following steps:
[0019] Step 1: subjecting the prepared ammonia nitrogen adsorption material to a temperature of 20 to 25°C and 100 to 140 r·min. -1 Under the condition of 22~26h, 20mg·L-1 NH4 + NH4 in -N solution + After -N adsorption, the soil is separated by centrifugation and then placed in an oven for drying to obtain soil improvement materials;
[0020] Step 2, uniformly mixing the soil improvement material with the soil at a ratio of 1‰ to 2‰ to obtain improved soil;
[0021] Step 3, soaking the seeds in deionized water for germination treatment, and planting the seeds after germination treatment in the above-mentioned improved soil;
[0022] Step 4: Water thoroughly for the first time and cultivate in a place with room temperature and sufficient light. Add water in equal amounts every two days, record the germination and growth of the seeds, and measure the soil pH and water holding capacity after completion.
[0023] The final improvement effect was that the soil seed germination rate was 60% to 70% when 1‰ to 2‰ soil improvement materials were added, the average plant height was 7.0 to 9.0 cm after one week, the soil pH was 7.46 to 7.92 after planting, and the water holding capacity was 22.82% to 24.37%.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] The present invention uses corn stalks and zeolite as raw materials, and prepares ammonia nitrogen (NH4 + -N) adsorption performance of loaded zeolite biochar materials, which can be used for low concentration NH4 + -N deep denitrification of wastewater, adsorption of NH4 + -N can be further used as soil conditioners to improve the physical and chemical properties of the soil, thereby promoting the germination and growth of plants. The significant advantages and technical effects are as follows: ① Using agricultural waste as raw materials, supplemented by cheap and readily available zeolite materials, we have developed efficient deep denitrification adsorption materials for low-concentration ammonia nitrogen wastewater, which can achieve the technical effect of using waste to treat pollution; ② Through the control of technical parameters, a composite functional material that has both low-concentration ammonia nitrogen wastewater adsorption and purification and soil improvement has been prepared, which can not only provide effective technical means for the denitrification treatment of sewage treatment plants, but also return the materials after nitrogen adsorption to the fields for soil improvement, achieving the beneficial technical effect of waste recycling, wastewater pollution control and coordinated soil improvement. ③ Through soil physical and chemical analysis, it was found that adding 1-2‰ of loaded zeolite biochar materials can improve the soil environment for spinach growth, reduce soil acidity, balance the water holding capacity of the soil, and help promote the germination and growth of spinach. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a SEM image of the microstructure of Example 1Z@C-OH8:2 of the present invention. DETAILED DESCRIPTION
[0027] The present invention is described in detail below in conjunction with the embodiments and drawings. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0028] Example 1, an ammonia nitrogen adsorption material that can be used for soil improvement, the raw materials of which include straw chips and zeolite powder in a mass ratio of 8:2;
[0029] The straw debris is corn stalks collected in Qinghai Province, air-dried and stored at room temperature; dried overnight before preparing biochar, crushed and sieved through a 100-mesh sieve to obtain straw debris;
[0030] The zeolite is natural clinoptilolite, which is ground and passed through a 200-mesh sieve to obtain zeolite powder.
[0031] A method for preparing an ammonia nitrogen adsorption material that can be used for soil improvement comprises the following steps:
[0032] S1. Evenly mixing straw scraps and zeolite powder to obtain a mixed raw material, wherein the mass ratio of straw scraps to zeolite powder is 8:2;
[0033] S2, the mixed raw materials obtained in step S1 are placed in a high temperature tube furnace for co-pyrolysis at 10 ° C. min -1 The temperature of the furnace was raised to 500°C with a temperature gradient of 100°C and kept at this temperature for 1 hour, during which nitrogen was introduced as a protective gas to isolate oxygen. During the pyrolysis process, zeolite and corn straw underwent a co-pyrolysis reaction to obtain a composite co-pyrolysis product named Z@C 8:2.
[0034] The composite co-pyrolysis product Z@C 8:2 is heated at 22°C and 120 r / min. -1 Under the condition of 24h, 20mg·L -1 NH4 + -N solution NH4 + -N maximum adsorption capacity is 17.22 mg / g;
[0035] S3, adding 0.2% of the composite co-pyrolysis product obtained in step S2 to a 1 mol / L NaOH solution, stirring evenly at 23°C and 120 r·min -1 After being shaken and immersed for 24 hours under the conditions of , the mixture was taken out, washed repeatedly with deionized water until it became neutral, and dried in a drying oven to obtain an alkali-modified product, namely, an ammonia nitrogen adsorption material, named Z@C-OH 8:2.
[0036] The alkali-modified product Z@C-OH 8:2 is heated to 22°C and 120 r·min. -1 Under the condition of 24h, 20mg·L -1 NH4 + -N solution NH4 + The maximum adsorption capacity of -N is 19.08 mg / g.
[0037] The microstructure of the Z@C-OH8:2 material in this example is shown in Figure 1 It can be seen that the material surface is smooth, and contains slits and mesopores inside, with NH4 + -N is a favorable site for attachment, and no other tiny particles are obviously attached. Zeolite particles are attached to the surface of biochar or embedded in the pores of biochar.
[0038] Example 2, an ammonia nitrogen adsorption material that can be used for soil improvement, the raw materials of which include straw chips and zeolite powder in a mass ratio of 7:3;
[0039] The straw debris is corn stalks collected in Qinghai Province, air-dried and stored at room temperature; dried overnight before preparing biochar, crushed and sieved through an 80-mesh sieve to obtain straw debris;
[0040] The zeolite is natural clinoptilolite, which is ground and passed through a 170-mesh sieve to obtain zeolite powder.
[0041] A method for preparing an ammonia nitrogen adsorption material that can be used for soil improvement comprises the following steps:
[0042] S1. Evenly mixing straw scraps and zeolite powder to obtain a mixed raw material, wherein the mass ratio of straw scraps to zeolite powder is 7:3;
[0043] S2, the mixed raw materials obtained in step S1 are placed in a high temperature tube furnace for co-pyrolysis at 10 ° C. min -1 The furnace temperature was raised to 750°C with a temperature gradient of 1.5°C and kept at this temperature for 2 hours, during which nitrogen was introduced as a protective gas to isolate oxygen. During the pyrolysis process, zeolite and corn straw underwent co-pyrolysis reaction to obtain a composite co-pyrolysis product named Z@C 7:3.
[0044] The composite co-pyrolysis product Z@C 7:3 is heated at 20°C and 120 r·min -1 Under the condition of 22h, 20mg·L -1 NH4 + -N solution NH4 + -N maximum adsorption capacity is 17.08 mg / g;
[0045] S3, adding 0.3% of the composite co-pyrolysis product obtained in step S2 to a 1 mol / L NaOH solution, stirring evenly at 25°C and 100 r·min -1 After being shaken and immersed for 26 hours under the conditions of , the mixture was taken out, washed repeatedly with deionized water until it became neutral, and dried in a drying oven to obtain an alkali-modified product, namely, an ammonia nitrogen adsorption material, named Z@C-OH 7:3.
[0046] The alkali-modified product Z@C-OH 7:3 is at 20°C and 100 r·min -1 Under the condition of 26h, 20mg·L -1 NH4 + -N solution NH4 + The maximum adsorption capacity of -N is 18.93 mg / g.
[0047] Example 3, an ammonia nitrogen adsorption material that can be used for soil improvement, the raw materials of which include straw chips and zeolite powder in a mass ratio of 9:1;
[0048] The straw debris is corn stalks collected in Qinghai Province, air-dried and stored at room temperature; dried overnight before preparing biochar, crushed and sieved through a 120-mesh sieve to obtain straw debris;
[0049] The zeolite is natural clinoptilolite, which is ground and passed through a 230-mesh sieve to obtain zeolite powder.
[0050] A method for preparing an ammonia nitrogen adsorption material that can be used for soil improvement comprises the following steps:
[0051] S1. Evenly mixing straw scraps and zeolite powder to obtain a mixed raw material, wherein the mass ratio of straw scraps to zeolite powder is 9:1;
[0052] S2, the mixed raw materials obtained in step S1 are placed in a high temperature tube furnace for co-pyrolysis at 10 ° C. min -1 The temperature of the furnace was raised to 600℃ with a temperature gradient of 1.5 hours, and the temperature was kept for 1.5 hours. During this period, nitrogen was introduced as a protective gas to isolate oxygen. During the pyrolysis process, zeolite and corn straw underwent co-pyrolysis reaction to obtain a composite co-pyrolysis product named Z@C 9:1.
[0053] The composite co-pyrolysis product Z@C 9:1 is heated at 25°C and 140 r·min -1 Under the condition of 22h, 20mg·L -1 NH4 + -N solution NH4 + -N maximum adsorption capacity is 16.81 mg / g;
[0054] S3, adding 0.1% of the composite co-pyrolysis product obtained in step S2 to a 1 mol / L NaOH solution, stirring evenly at 20°C and 140 r·min -1 After being shaken and immersed for 22 hours under the conditions of , the mixture was taken out, washed repeatedly with deionized water until it became neutral, and dried in a drying oven to obtain an alkali-modified product, namely, an ammonia nitrogen adsorption material, named Z@C-OH 9:1.
[0055] The alkali-modified product Z@C-OH 9:1 is heated to 25°C and 140 r·min. -1 Under the condition of 22h, 20mg·L -1 NH4 + -N solution NH4 + The maximum adsorption capacity of -N is 17.89 mg / g.
[0056] Comparative Example 1, an ammonia nitrogen adsorption material, the raw materials of which include straw chips and zeolite powder in a mass ratio of 1:1;
[0057] The straw debris is corn stalks collected in Qinghai Province, air-dried and stored at room temperature; dried overnight before preparing biochar, crushed and sieved through a 100-mesh sieve to obtain straw debris;
[0058] The zeolite is natural clinoptilolite, which is ground and passed through a 200-mesh sieve to obtain zeolite powder.
[0059] A method for preparing an ammonia nitrogen adsorption material comprises the following steps:
[0060] S1, uniformly mixing straw scraps and zeolite powder to obtain a mixed raw material, wherein the mass ratio of the straw scraps to the zeolite powder is 1:1;
[0061] S2, the mixed raw materials obtained in step S1 are placed in a high temperature tube furnace for co-pyrolysis at 10 ° C. min -1 The temperature of the furnace was raised to 500°C with a temperature gradient of 1:1 and kept at this temperature for 1 hour, during which nitrogen was introduced as a protective gas to isolate oxygen. During the pyrolysis process, zeolite and corn straw underwent a co-pyrolysis reaction to obtain a composite co-pyrolysis product, named Z@C1:1.
[0062] The composite co-pyrolysis product Z@C1:1 is heated to 22°C and 120 r·min -1 Under the condition of 24h, 20mg·L -1 NH4 + -N solution NH4 + -N maximum adsorption capacity is 7.59 mg / g;
[0063] S3, adding 0.2% of the composite co-pyrolysis product obtained in step S2 to a 1 mol / L NaOH solution, stirring evenly at 25°C and 120 r·min -1 After being shaken and immersed for 24 hours under the conditions of , the mixture was taken out, washed repeatedly with deionized water until it became neutral, and dried in a drying oven to obtain an alkali-modified product, namely, an ammonia nitrogen adsorption material, named Z@C-OH 1:1.
[0064] The alkali-modified product Z@C-OH 1:1 is at 22°C and 120 r·min -1 Under the condition of 24h, 20mg·L -1 NH4 + -N solution NH4 + The maximum adsorption capacity of -N is 8.21 mg / g.
[0065] Comparative Example 2, an ammonia nitrogen adsorption material, the raw materials of which include straw chips and zeolite powder in a mass ratio of 3:7;
[0066] The straw debris is corn stalks collected in Qinghai Province, air-dried and stored at room temperature; dried overnight before preparing biochar, crushed and sieved through a 100-mesh sieve to obtain straw debris;
[0067] The zeolite is natural clinoptilolite, which is ground and passed through a 200-mesh sieve to obtain zeolite powder.
[0068] A method for preparing an ammonia nitrogen adsorption material comprises the following steps:
[0069] S1, uniformly mixing straw scraps and zeolite powder to obtain a mixed raw material, wherein the mass ratio of straw scraps to zeolite powder is 3:7;
[0070] S2, the mixed raw materials obtained in step S1 are placed in a high temperature tube furnace for co-pyrolysis at 10 ° C. min -1 The temperature of the furnace was raised to 500°C with a temperature gradient of 1°C and kept at this temperature for 1 hour, during which nitrogen was introduced as a protective gas to isolate oxygen. During the pyrolysis process, zeolite and corn straw underwent a co-pyrolysis reaction to obtain a composite co-pyrolysis product named Z@C3:7.
[0071] The composite co-pyrolysis product Z@C3:7 is heated to 22°C and 120 r·min -1 Under the condition of 24h, 20mg·L -1 NH4 + -N solution NH4 + -N maximum adsorption capacity is 8.91 mg / g;
[0072] S3, adding 0.2% of the composite co-pyrolysis product obtained in step S2 to a 1 mol / L NaOH solution, stirring evenly at 25°C and 120 r·min -1 After being shaken and immersed for 24 hours under the conditions of , the mixture was taken out, washed repeatedly with deionized water until it became neutral, and dried in a drying oven to obtain an alkali-modified product, namely, an ammonia nitrogen adsorption material, named Z@C-OH 3:7.
[0073] The alkali-modified product Z@C-OH 3:7 is heated at 22°C and 120 r·min. -1 Under the condition of 24h, 20mg·L -1 NH4 + -N solution NH4 + The maximum adsorption capacity of -N is 9.43 mg / g.
[0074] The maximum ammonia nitrogen adsorption capacity of Examples 1-3 and Comparative Examples 1-2 is compared in Table 1. It can be seen that under the conditions of Example 1, Z@C 8:2 before alkali modification and Z@C-OH 8:2 after alkali modification have a higher adsorption capacity for NH4 + -N has the best adsorption effect.
[0075] Table 1
[0076]
[0077] Application Example 1: Application of an ammonia nitrogen adsorption material for soil improvement described in Example 1 to adsorb NH4 + -N-containing materials are added to the soil in an appropriate amount to improve soil properties and promote plant germination and growth; the application method comprises the following steps:
[0078] Step 1: The ammonia nitrogen adsorption material Z@C-OH 8:2 prepared above was heated at 22°C and 120 r·min -1 Under the condition of 24h, 20mg·L -1 NH4 + NH4 in -N solution + After -N adsorption, the soil is separated by centrifugation and then placed in an oven for drying to obtain soil improvement materials;
[0079] Step 2, uniformly mixing the soil improvement material with the soil at a ratio of 1‰ to obtain improved soil;
[0080] Step 3, soaking the spinach seeds in deionized water for germination treatment, and planting the germination-treated spinach seeds in the above-mentioned improved soil;
[0081] Step 4: Water thoroughly for the first time and cultivate in a place with room temperature and sufficient light. Add water in equal amounts every two days, record the germination and growth of the seeds, and measure the soil pH and water holding capacity after completion.
[0082] The final improvement effect was that the soil seed germination rate was 70% when 1‰ soil improvement material was added, the average plant height was 9.0cm after one week, the soil pH was 7.46 after planting, and the water holding capacity was 22.82%.
[0083] Application Example 2: The ammonia nitrogen adsorption material Z@C-OH 8:2 prepared in Example 1 was heated at 20°C and 100 r·min -1 Under the condition of 26h, 20mg·L -1 NH4 + NH4 in -N solution + After -N adsorption, the soil improvement material is obtained by centrifugal separation and then placed in an oven for drying; the soil improvement material is evenly mixed with the soil at a ratio of 2‰, and the rest is the same as in Application Example 1.
[0084] The final improvement effect was that the soil seed germination rate was 60% when 2‰ soil improvement material was added, the average plant height was 7.0cm after one week, the soil pH was 7.92 after planting, and the water holding capacity was 24.37%.
[0085] Application Example 3: The ammonia nitrogen adsorption material Z@C-OH 8:2 prepared in Example 1 was heated at 25°C and 140 r·min -1 Under the condition of 22h, 20mg·L -1 NH4 + NH4 in -N solution + After -N adsorption, the soil improvement material is obtained by centrifugal separation and then placed in an oven for drying; the soil improvement material is evenly mixed with the soil at a ratio of 1.5‰, and the rest is the same as in Application Example 1.
[0086] The final improvement effect was that the soil seed germination rate was 62.5% when 1.5‰ soil improvement material was added, the average plant height was 7.6cm after one week, the soil pH was 7.62 after planting, and the water holding capacity was 23.58%.
[0087] In the comparative example 1, the soil improvement material and the soil were uniformly mixed at 0‰, and the rest was the same as in the application example 1.
[0088] The final effect was a soil seed germination rate of 40%, an average plant height of 6.5 cm after one week, a soil pH of 6.82 after planting, and a water holding capacity of 26.09%.
[0089] In application example 2, the soil improvement material and the soil are uniformly mixed at a ratio of 0.5‰, and the rest is the same as in application example 1.
[0090] The final improvement effect was that the germination rate of seeds in the soil with 0.5‰ soil improvement material was 30%. The average plant height was 6.0cm after one week. The soil pH after planting was 7.15 and the water holding capacity was 26.03%.
[0091] In application example 3, the soil improvement material and the soil are uniformly mixed at a ratio of 3‰, and the rest is the same as in application example 1.
[0092] The final improvement effect was that the germination rate of seeds in the soil with 3‰ soil improvement material was 35%. The average plant height was 6.0cm after one week. The soil pH after planting was 8.01 and the water holding capacity was 29.67%.
[0093] The soil improvement effects of application examples 1-3 and comparative application examples 1-3 are compared in Table 2. From the aspects of soil seed germination rate, average plant height, soil pH and water holding capacity, it can be seen that compared with other application examples, application example 1 with the addition of 1‰ soil improvement material has the best soil improvement effect.
[0094] Table 2
[0095]
[0096] The application effects of Embodiment 2 and Embodiment 3 of the present invention are similar to that of Embodiment 1.
Claims
1. An ammonia nitrogen adsorption material that can be used for soil improvement, characterized in that: The raw materials include straw chips and zeolite powder in a mass ratio of 7:3-9:
1. The straw debris is corn stalks, which are air-dried and stored at room temperature after being collected. Before preparing biochar, they are dried overnight, crushed and sieved through an 80-120 mesh sieve to obtain straw debris. The zeolite is natural clinoptilolite, which is ground and passed through a 170-230 mesh sieve to obtain zeolite powder.
2. The method for preparing an ammonia nitrogen adsorption material that can be used for soil improvement according to claim 1, characterized in that: The following steps are involved: S1. Evenly mixing straw scraps and zeolite powder to obtain a mixed raw material, wherein the mass ratio of straw scraps to zeolite powder is 7:3-9:1; S2, the mixed raw materials obtained in step S1 are placed in a high temperature tube furnace for co-pyrolysis at 10 ° C. min -1 The temperature of the furnace is raised to 500-750°C with a temperature gradient of 100°C and kept at this temperature for 1-2 hours, during which nitrogen is introduced as a protective gas to isolate oxygen; during the pyrolysis process, zeolite and corn stalks undergo a co-pyrolysis reaction to obtain a composite co-pyrolysis product; S3, adding 0.1-0.3% of the composite co-pyrolysis product obtained in step S2 to a 1 mol / L NaOH solution, stirring evenly at 20-25°C and 100-140 r·min -1 After being shaken and immersed for 22 to 26 hours under the conditions of , it is taken out, repeatedly washed with deionized water until it becomes neutral, and placed in a drying oven for drying to obtain an alkali-modified product, i.e., an ammonia nitrogen adsorption material.
3. The preparation method according to claim 2, characterized in that: The composite co-pyrolysis product is heated at 20-25°C and 100-140 r / min. -1 Under the condition of 22~26h, 20mg·L -1 NH4 + -N solution NH4 + The maximum adsorption capacity of -N is 16.84~17.22mg / g.
4. The preparation method according to claim 2, characterized in that: The alkali-modified product is heated at 20-25°C and 100-140 r·min. -1 Under the condition of 22~26h, 20mg·L -1 NH4 + -N solution NH4 + The maximum adsorption capacity of -N is 17.89-19.08 mg / g.
5. The use of an ammonia nitrogen adsorption material for soil improvement prepared according to claim 2, characterized in that: Will adsorb NH4 + -N-containing materials are added to the soil to improve soil properties and promote plant germination and growth.
6. The application method according to claim 5, characterized in that: The following steps are involved: Step 1: subjecting the prepared ammonia nitrogen adsorption material to a temperature of 20 to 25°C and 100 to 140 r·min. -1 Under the condition of 22~26h, 20mg·L -1 NH4 + NH4 in -N solution + After -N adsorption, the soil is separated by centrifugation and then placed in an oven for drying to obtain soil improvement materials; Step 2, uniformly mixing the soil improvement material with the soil at a ratio of 1‰ to 2‰ to obtain improved soil; Step 3, soaking the seeds in deionized water for germination treatment, and planting the seeds after germination treatment in the above-mentioned improved soil; Step 4: Water thoroughly for the first time and cultivate in a place with room temperature and sufficient light. Add water in equal amounts every two days, record the germination and growth of the seeds, and measure the soil pH and water holding capacity after completion.
7. The application method according to claim 6, characterized in that: The final improvement effect was that the soil seed germination rate was 60% to 70% when 1‰ to 2‰ soil improvement materials were added, the average plant height was 7.0 to 9.0 cm after one week, the soil pH was 7.46 to 7.92 after planting, and the water holding capacity was 22.82% to 24.37%.
8. An ammonia nitrogen adsorption material that can be used for soil improvement, characterized in that: Its raw materials include straw chips and zeolite powder in a mass ratio of 8:2; The straw debris is corn stalks collected in Qinghai Province, air-dried and stored at room temperature; dried overnight before preparing biochar, crushed and sieved through a 100-mesh sieve to obtain straw debris; The zeolite is natural clinoptilolite, which is ground and passed through a 200-mesh sieve to obtain zeolite powder.
9. The method for preparing an ammonia nitrogen adsorption material for soil improvement according to claim 8, characterized in that: The following steps are involved: S1. Evenly mixing straw scraps and zeolite powder to obtain a mixed raw material, wherein the mass ratio of straw scraps to zeolite powder is 8:2; S2, the mixed raw materials obtained in step S1 are placed in a high temperature tube furnace for co-pyrolysis at 10 ° C. min -1 The temperature of the furnace was raised to 500°C with a temperature gradient of 100°C and kept at this temperature for 1 hour, during which nitrogen was introduced as a protective gas to isolate oxygen. During the pyrolysis process, zeolite and corn straw underwent a co-pyrolysis reaction to obtain a composite co-pyrolysis product named Z@C 8:
2. The composite co-pyrolysis product Z@C 8:2 is heated at 22°C and 120 r / min. -1 Under the condition of 24h, 20mg·L -1 NH4 + -N solution NH4 + -N maximum adsorption capacity is 17.22 mg / g; S3, adding 0.2% of the composite co-pyrolysis product obtained in step S2 to a 1 mol / L NaOH solution, stirring evenly at 23°C and 120 r·min -1 After being shaken and immersed for 24 hours under the conditions of , the product was taken out, washed repeatedly with deionized water until it became neutral, and dried in a drying oven to obtain an alkali-modified product, i.e., an ammonia nitrogen adsorption material, named Z@C-OH 8:2; The alkali-modified product Z@C-OH 8:2 is heated to 22°C and 120 r·min. -1 Under the condition of 24h, 20mg·L -1 NH4 + -N solution NH4 + The maximum adsorption capacity of -N is 19.08 mg / g.
10. Use of an ammonia nitrogen adsorption material for soil improvement prepared according to claim 9, characterized in that: Will adsorb NH4 + -N-containing materials are added to the soil in an appropriate amount to improve soil properties and promote plant germination and growth; the application method includes the following steps: Step 1: The ammonia nitrogen adsorption material Z@C-OH 8:2 prepared above was heated at 22°C and 120 r·min -1 Under the condition of 24h, 20mg·L -1 NH4 + NH4 in -N solution + After -N adsorption, the soil is separated by centrifugation and then placed in an oven for drying to obtain soil improvement materials; Step 2, uniformly mixing the soil improvement material with the soil at a ratio of 1‰ to obtain improved soil; Step 3, soaking the spinach seeds in deionized water for germination treatment, and planting the germination-treated spinach seeds in the above-mentioned improved soil; Step 4: Water thoroughly for the first time, place the seeds in a room temperature and well-lit place for cultivation, add water in equal amounts every two days, record the germination and growth of the seeds, and measure the soil pH and water holding capacity after completion; The final improvement effect was that the soil seed germination rate was 70% when 1‰ soil improvement material was added, the average plant height was 9.0cm after one week, the soil pH was 7.46 after planting, and the water holding capacity was 22.82%.
Citation Information
Patent Citations
Method for preparing biomass charcoal-based slow-release organic fertilizer through agricultural solid waste
CN106588274A
Production method of corn straw pyrolysis biochar soil conditioner
CN109384628A
Ultrasonic activated biochar as well as preparation method and application thereof
CN113019323A
Artificial wetland for plants and compound matrix under action of low-temperature intermittent aeration
CN118388051A
Silicon-calcium modified biochar composite material as well as preparation method and application thereof
CN119158543A
Cited By
Matrix improvement and pioneer plant combined tungsten tailing ecological restoration method
CN120662640A